An approach to teaching assembly language, computer architecture, and organization - Borin, Edson; Auler, Rafael (International Journal of Computer Architecture Education, 2013)
In this article, we present an approach to teaching assembly language, computer architecture, and organization, and discuss the use of this approach in computer science and engineering courses at the University of Campinas.